Antileukotrienes in the treatment of bronchial asthma in children: expected and real success - Y. L. Mizernitsky (Медицинский совет, 2014)
The article summarizes current evidence on the role of leukotrienes in the pathogenesis of asthma in children and antileukotriene drugs in the treatment of the disease. Indications and prospects for the use of montelukast in the treatment of bronchial asthma in children are defined.